Fabrication of silver nanoparticles on glass substrate using low-temperature rapid thermal annealing. Issue 3 (May 2018) - Barman, Bidyut; Dhasmana, Hrishikesh; Verma, Abhishek; Kumar, Amit; Singh, DN; Jain, VK
Metallic nanoparticle-based localized surface plasmon resonance phenomenon is of great interest in the field of solar cells and can increase efficiency via solar energy harvesting in the device due to their light trapping capabilities. In present research, rapid thermal annealing, a modern physical technique, has been employed for the fabrication of silver nanoparticles on glass substrates at lower temperature regime. The rapid thermal annealing is carried at temperatures 200, 250, and 300°C for annealing duration of 5, 10, 15, 20, and 30 min of as-sputtered silver clusters and then kept for natural cooling in inert ambient which has resulted into formation of silver nanoparticles on glass substrate. The surface morphological analysis of the grown silver nanoparticles shows average particle size minimization behavior with increase in rapid thermal annealing up to 15 min duration. Thereafter an increase in average size is observed with rapid thermal annealing time duration up to 30 min for all rapid thermal annealing temperatures. A growth mechanism is suggested to explain observed changes in silver nanoparticles size behavior under rapid thermal annealing conditions. The respective absorption peaks are lying in the wavelength range of 400–500 nm which confirms the formation of silver nanoparticles. The optical study for respective size of silver nanoparticles has also been analyzed and compared with that of theoretical calculations from Mie scattering theory.